PATHOGENESIS AND ETIOLOGY OF CHRONIC MYELOPROLIFERATIVE NEOPLASMS (CMPNS): A COMPREHENSIVE REVIEW - Jakhonov Azizbek Kholmirzaevich; Matkarimova Dilfuza Saburovna (TADQIQOTLAR, 2025)
Abstract Chronic myeloproliferative neoplasms (CMPNs) are a heterogeneous group of hematopoietic stem cell disorders characterized by the clonal proliferation of one or more myeloid lineages. The main subtypes include chronic myeloid leukemia (CML), polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). These disorders share common pathogenic mechanisms, often involving mutations in genes such as JAK2, CALR, and MPL, leading to dysregulated signaling pathways and abnormal hematopoiesis. This review summarizes the current understanding of the etiology and pathogenesis of CMPNs, highlighting molecular mechanisms, clinical manifestations, diagnostic criteria, and potential therapeutic targets.